2015
DOI: 10.1039/c5ra05409e
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of ultrafine metal oxide/carbon and metal carbide/carbon nanocomposite fibers

Abstract: Electrospinning is a facile technology for the generation of metal oxide/carbon and metal carbide/carbon nanocomposite fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…In addition, literature review showed that ZrC nanofibrous mesh has a good potential for various applications such as thermal storage packages and wear‐resistant coatings due to its high strength and thermal shock resistance . ZrC nanofibers have been synthesized via electrospinning technique using different zirconium and carbon sources such as zirconium acetyl acetonate (ZrAcAc), phenolic resins, zirconium (IV) acetyl acetonate, cellulose acetate, water‐soluble zirconium compound (ZC), poly(vinyl alcohol) (PVA) and zirconium oxychloride octahydrate, polyacrylonitrile (PAN), respectively . Up to now, the thinnest ZrC fibers were synthesized with the mean diameter of 710 nm after carbothermal reduction at 1600°C using ZrAcAc, cellulose acetate, and acetic acid to stabilize the sol .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, literature review showed that ZrC nanofibrous mesh has a good potential for various applications such as thermal storage packages and wear‐resistant coatings due to its high strength and thermal shock resistance . ZrC nanofibers have been synthesized via electrospinning technique using different zirconium and carbon sources such as zirconium acetyl acetonate (ZrAcAc), phenolic resins, zirconium (IV) acetyl acetonate, cellulose acetate, water‐soluble zirconium compound (ZC), poly(vinyl alcohol) (PVA) and zirconium oxychloride octahydrate, polyacrylonitrile (PAN), respectively . Up to now, the thinnest ZrC fibers were synthesized with the mean diameter of 710 nm after carbothermal reduction at 1600°C using ZrAcAc, cellulose acetate, and acetic acid to stabilize the sol .…”
Section: Introductionmentioning
confidence: 99%
“…All the chemicals will be completely dissolved by stirring for 15 h at room temperature. The electrospinning is undertaken using a MECC nanofiber electrospinner15 . The parameters are shown in the table below.…”
mentioning
confidence: 99%
“…Atchison et al [44] prepared metal carbide-supported carbon nanocomposites through carbothermal reduction process. Zirconium carbide/carbon nanocomposite (ZrC/C), titanium carbide/carbon nanocomposite (TiC/C), and niobium carbide/ carbon nanocomposite (NbC/C) were prepared by electrospinning followed by carbothermal reduction at elevated temperatures.…”
Section: Carbon Nanofiber Compositesmentioning
confidence: 99%
“…Alike, electrospun Ag/g-C 3 N 4 -loaded composite carbon nanofibers (Ag/g-C 3 N 4 / CNFs) were used for the conversion of 4-nitrophenol to 4-aminophenol and benzylamine to N-benzylbenzaldimine [44]. The Ag/g-C 3 N 4 /CNFs offered the significant advantages, such as low catalyst use, high activity, easy recycling, and excellent stability.…”
Section: Carbon Nanocomposites In Organic Transformationsmentioning
confidence: 99%